Indicated Prevention for Incoming Freshmen: Personalized Normative Feedback and High-Risk Drinking - Lewis, Melissa A. (2007)
This research evaluated the efficacy of a computerized, freshmen-specific personalized normative feedback (PNF) intervention on reducing alcohol consumption among high-risk drinking freshmen. Students (N = 316; 53.8% female) completed measures of perceived drinking norms and drinking behavior. After completing the baseline assessment, students were randomly assigned to receive either freshmen-specific PNF that was gender-specific or gender-neutral, or to assessment only control. Findings demonstrated that students exhibited normative misperceptions for typical freshmen drinking behavior and that perceptions of typical same-sex freshmen drinking were positively associated with riskier drinking behavior. At follow-up, students randomly assigned to receive PNF reduced perceptions of typical freshmen drinking behavior and personal drinking behavior relative to those who did not receive PNF. Findings extend previous evaluations of computer-based PNF and suggest that computer-based PNF for incoming freshmen using utilizing freshmen-specific norms that are gender-specific may constitute a promising prevention strategy.